Complexity and Organizational Architecture. - Ioannides, Yannis Menelaos. (Tufts University. Tisch Library., 2016)
This paper examines how architectural features of organizations, that are made up of individuals screening projects, affect organizational screening performance. The paper explores consequences for organizational design of a theorem (attributed to Von Neumann by Moore and Shannon) on how to build reliable networks using unreliable components. The paper examines general properties of committee decision making and shows the superiority of committees with respect to composition, that is when each member of organization is replaced by a replica of the entire organization. The paper links with the modern Condorcet Jury Theorem literature. It also shows that screening performance is sigmoid in individual screening performance for hierarchies of polyarchies and for polyarchies of hierarchies. The supermodularity and sub-modularity properties of those structures allows us to link with results from the theory of teams. The screening performance is also sigmoid for a cognitive model that allows for individuals' own screening to be influenced by screening decisions of superiors and of subordinates. The paper examines the implications of such features for the limits to organizational performance.